Simplifying the Animal Welfare Assessment Grid for enhanced accessibility - Kim, Ji-yoon; Choi, Jae-Hyeon; Ryu, HyunYoung; Kang, Hye-Jin (Frontiers in Veterinary Science, 2024)
Ensuring animal welfare is essential for both the well-being of zoo animals and the effective management of zoological facilities. This study introduces the Simplified Animal Welfare Assessment Grid (S-AWAG), a streamlined adaptation of the original AWAG framework that integrates the Five Domains Model with an observation-based approach. Designed for non-expert users, S-AWAG focuses on easily observable welfare indicators—such as health and environmental conditions—making it particularly suitable for small, private zoos, including petting zoos, roadside zoos, indoor zoos, and animal cafés. We conducted welfare assessments on 304 animals from 11 species across nine zoos in South Korea. The results revealed significant differences in welfare standards between accredited and non-accredited zoos, with accredited facilities consistently demonstrating better welfare conditions (p < 0.05). The tool exhibited high inter-rater reliability (IRR = 0.839), confirming its consistency across assessors with varying levels of expertise and ensuring reliable and accurate results. Pearson correlation analysis identified strong positive associations between health and environmental factors, reinforcing the comprehensive nature of the tool’s evaluation approach. With its user-friendly, efficient, and adaptable design, S-AWAG has the potential to improve animal welfare standards not only in South Korea but also globally, particularly in smaller, resource-constrained facilities.